(untitled) (Bangladesh Journal of Public Administration, 2020)
Government servants receive pension after their retirement in exchange for their services to the state during their service life. But the structural change in every National Pay Scale influences the amount of net pension they receive. So the objectives of this study were set to examine the pay structures of the last five National Pay Scales to find out if there is any inequality in the net pension of all government servants and to recommend policy intervention for ensuring equity in the existing pension system. Secondary data were collected from the last five consecutive National Pay Scales and IBAS++ of Finance Division and analyzed them by using the basic statistical method to probe into the objectives of the paper. After analysis of data, it appeared that inequality exists in the net pension of all retired government servants. Therefore, the paper recommends that the amounts of net pension that the pensioners are receiving based on the National Pay Scales of 1991, 1997, 2005 and 2009 should be increased on average by 68%, 54%, 46%, and 38% respectively to equalize them with the net pension on July 1, 2015, calculated based on the National Pay Scales of 2015. It also recommends that in this regard, the government should consider framing an equitable, fair, and sustainable pension policy. Keywords: Equity, equality, pay, pension, retired, servants